-89=1+8(7/4p+1)

Simple and best practice solution for -89=1+8(7/4p+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -89=1+8(7/4p+1) equation:



-89=1+8(7/4p+1)
We move all terms to the left:
-89-(1+8(7/4p+1))=0
Domain of the equation: 4p+1))!=0
p∈R
We multiply all the terms by the denominator
-(1+8(7-89*4p+1))=0
We calculate terms in parentheses: -(1+8(7-89*4p+1)), so:
1+8(7-89*4p+1)
determiningTheFunctionDomain 8(7-89*4p+1)+1
We add all the numbers together, and all the variables
8(-89*4p+8)+1
We multiply parentheses
-2848p+64+1
We add all the numbers together, and all the variables
-2848p+65
Back to the equation:
-(-2848p+65)
We get rid of parentheses
2848p-65=0
We move all terms containing p to the left, all other terms to the right
2848p=65
p=65/2848
p=65/2848

See similar equations:

| -6x=1x+-29 | | -13.16=4.88+4j | | -7x+23=-15 | | 114/f=8 | | 637/48=19/6n+5/8n | | x–(5–2.x)=35 | | x–(5–2x)=35 | | 4p+16=32 | | 62+5x-4+x-2=180 | | 4(20+5x)=60 | | 13z-(z+21)=39 | | -6p+6-3=-21 | | -2x-4=-2x-3-1 | | 15=(a)/(3)-2 | | 6(k−7)=18 | | -1/3-8/5b=463/195 | | Y=-5+1/2x | | 2(f+10)=32 | | 5(d+9)=65 | | 5x-20=5x-12 | | 3(2x-1)=6x-8+x | | 90=6xL | | 7*(10-3x)=5*(15-4x) | | 1.4x-7=-5x+20 | | ½÷¾=x+4x | | −3x−1=8x+34 | | 1/2(8x+22)=x+11+3x | | 5*b=75 | | 64=4x+24+4x | | 4(w–3)=20 | | -1(x-3)=8x | | 6x-5+9x=7 |

Equations solver categories